GPR40 Activation Abolishes Diabetes-Induced Painful Neuropathy by Suppressing VEGF-A Expression - Königs, Vanessa; Pierre, Sandra; Schicht, Martin; Welss, Jessica; Hahnefeld, Lisa; Rimola, Vittoria; Lütjen-Drecoll, Elke; Geisslinger, Gerd; Scholich, Klaus (Diabetes, 2022)
G-protein-coupled receptor 40 (GPR40) is a promising target to support glucose-induced insulin release in patients with type 2 diabetes. We studied the role of GPR40 in the regulation of blood-nerve barrier integrity and its involvement in diabetes-induced neuropathies. Because GPR40 modulates insulin release, we used the streptozotocin model for type 1 diabetes, in which GPR40 functions can be investigated independently of its effects on insulin release. Diabetic wild-type mice exhibited increased vascular endothelial permeability and showed epineural microlesions in sciatic nerves, which were also observed in naïve GPR40-/- mice. Fittingly, expression of vascular endothelial growth factor-A (VEGF-A), an inducer of vascular permeability, was increased in diabetic wild-type and naïve GPR40-/- mice. GPR40 antagonists increased VEGF-A expression in murine and human endothelial cells as well as permeability of transendothelial barriers. In contrast, GPR40 agonists suppressed VEGF-A release and mRNA expression. The VEGF receptor inhibitor axitinib prevented diabetes-induced hypersensitivities and reduced endothelial and epineural permeability. Importantly, the GPR40 agonist GW9508 reverted established diabetes-induced hypersensitivity, an effect that was blocked by VEGF-A administration. Thus, GPR40 activation suppresses VEGF-A expression, thereby reducing diabetes-induced blood-nerve barrier permeability and reverting diabetes-induced hypersensitivities.
CRIS-Team Scopus Importer:2022-04-22